(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper reports results of the study of the distribution profiles of implanted iron and cobalt atoms in silicon as a function of the radiation dose and annealing temperature that was performed by applying the Rutherford backscattering spectroscopy (RBS). The effects of thermal annealing on the distribution of iron, cobalt, and in particular oxygen were studied. The authors strongly suggest that under certain heat treatment conditions and by applying specific radiation doses, the so-called epitaxial silicides will build on the surface of a single crystal, which can play the role of conducting or metal layers. One could consider theRBS method for analysis of both the topological distribution of dopants and the interaction of impurities.